Informing craft producers in South Africa - Khathutshelo Mercy Makhitha; Melanie Wiese; Gené van Heerden (Communicare)
Craft producers struggle to access the retail market because of their inability to communicate effectively. Understanding craft retailers’ buying behaviour, particularly with regard to the communication channels used, could potentially assist craft producers to create better awareness of their crafts. The purpose of this article is to investigate the communication channels used by formal craft retailers when searching for craft suppliers and craft products. A survey of formal craft retailers resulted in a total of 233 useable questionnaires. Principalcomponent factor analysis was used to identify the various types of communication channels while ANOVA analysis was applied to test the hypothesis. The results indicated that craft retailers differ in their use of certain communication channels and that they tend to use particular channels more often than others. The factor analysis identified three types of communication channels: internal and personal, promotional, and print advertising. The results further indicated that craft retailers consult internal and personal channels more frequently than promotional channels and print advertising. The results also revealed that different types of craft retailers differ in their preference of promotional channels, whereas no such differences could be found in the way these craft retailers used internal and personal channels or print advertising. The results presented in this article provide useful insights – especially to informal craft producers – on how to improve their visibility and product availability by communicating more effectively with formal craft retailers.